Case Study: Brazil’s investment in innovation for sustainable agricultural intensification - Dalberg Asia (Commission on Sustainable Agriculture Intensification, 2021)
Brazil has transformed from being a net food importer, to one of the largest agricultural exporters in the world. The country is now one of the top global funders of agricultural innovation, with a special emphasis on funding R&D for sustainable agriculture. While food insecurity and environmental challenges exist in many parts of Brazil, social programs and funding in innovation have helped those in need. The study of agriculture innovation funding and sustainable agriculture innovation funding patterns in Brazil becomes important to not only direct targeted funding within the country but also to inform other countries that might benefit from the country’s experience. This case study analyses overall funding flows into agriculture and SAI innovation in Brazil between 2010-2019.